Influence of bone morphology on the mechanobiological stimuli distribution of maxillary anterior labial bone: A biomechanical study. Issue 7 (8th June 2022) - Liao, Menglin; Wang, Chunjuan; Wang, Chao; Xu, Yamei
Abstract: Objective: This study intended to ascertain the dimensional effects of labial bone thickness and height on the mechanobiological stimuli distribution of maxillary anterior labial bone through biomechanical analysis. Material and methods: Twelve 3D finite element models of an anterior maxillary region with an implant were computer‐simulated, including four levels of labial bone thicknesses (2, 1.5, 1.0, and 0.5 mm) and three levels of labial bone heights (normal, reduced by 1/3, reduced by 1/2). A 45° buccolingual oblique load of 100 N was applied to the implant restoration. Results: Equivalent stress and principal strain mainly concentrated on crestal bone around the implant neck. The maximum equivalent stress in bone decreased as labial bone mass decreased, while the maximum principal strain and the displacement of dental implant increased as labial bone mass decreased. No significant difference of these three indicators was observed, when the labial bone thickness changed in the range of 2.0–1.0 mm with sufficient labial bone height. Conclusions: In terms of biomechanics, the thickness of labial bone plate was recommended ≥1 mm. Sufficient labial bone height was warranted to prevent the stability of the implants from being seriously affected. The labial bone heights were more effective than thicknesses on the mechanobiological stimuli response of the dental implant‐bone system. Clinical significance: For this 3D finite element study, the biomechanical responses under different bone mass conditions were explored, in order to predict the process of bone remodeling and provide valid clinical recommendations for the decision‐making process regarding the choices of tissue augmentation for some specific esthetic implantation cases for future clinical applications.